Abigail, the breeze fairy - Meadows, Daisy; Ripper, Georgie (New York : Scholastic, 2004)
Abigail the Breeze Fairy has been blown off-course without her wispy wind feather. Will Rachel and Kirsty be able to find the feather and bring calm to the blustery village?
"A Little Apple paperback."
Keywords: Fairies -- Juvenile fiction; Feathers -- Juvenile fiction; Lost articles -- Juvenile fiction; Weather -- Juvenile fiction; Villages -- Juvenile fiction; Fairies -- Fiction; Feathers -- Fiction; Lost and found possessions -- Fiction; Weather -- Fiction; Villages -- Fiction; Fantasy; Fantasy fiction